2021
DOI: 10.2166/aqua.2021.005
|View full text |Cite
|
Sign up to set email alerts
|

Microbial characterizations of water using tea polyphenols as a disinfectant for effluent treatment after the ultrafiltration process

Abstract: The microbial characteristics of water treated by tea polyphenols after the ultrafiltration process were studied based on the continuous disinfection performance of tea polyphenols. Metagenomics was carried out to investigate the microbial community distribution, functional characteristics, and variations after disinfection, to reveal the disinfection principle of tea polyphenols, and to provide the theoretical basis for using tea polyphenols as a disinfectant to better control the growth of microorganisms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although the concentration of microorganisms in the UF effluent is low, it is still necessary to add disinfectants to avoid secondary contamination of drinking water in the pipe network. Wei et al (2021) used an UF membrane with a pore size of 0.01 μm to explore the sterilizing effect of tea polyphenols at different concentrations on UF effluent. The results showed that tea polyphenols below 5.0 mg/L could not contain the bacterial concentration within the UF effluent at below 100 CFU/mL over 48 h. Therefore, in order to retain the lower dosage as far as possible, the optimal dosage for tea polyphenols as a disinfectant for UF effluent is 5.0 mg/L and the chromaticity of the effluent is 5.…”
Section: As the Main Disinfectant Of Uf Effluentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the concentration of microorganisms in the UF effluent is low, it is still necessary to add disinfectants to avoid secondary contamination of drinking water in the pipe network. Wei et al (2021) used an UF membrane with a pore size of 0.01 μm to explore the sterilizing effect of tea polyphenols at different concentrations on UF effluent. The results showed that tea polyphenols below 5.0 mg/L could not contain the bacterial concentration within the UF effluent at below 100 CFU/mL over 48 h. Therefore, in order to retain the lower dosage as far as possible, the optimal dosage for tea polyphenols as a disinfectant for UF effluent is 5.0 mg/L and the chromaticity of the effluent is 5.…”
Section: As the Main Disinfectant Of Uf Effluentmentioning
confidence: 99%
“…All indicators meet the requirements of the Drinking Water Sanitation Standard GB5749-2006 (Figure 4). To explore changes in the microbial community structure in water after UF-tea polyphenol disinfection, Wei et al (2021) used high-throughput sequencing to perform metagenomics analysis of disinfected water. The results showed that the proportion of Janthinobacterium that produce metabolites such as Violacein with antibacterial and antiviral activity increased after tea polyphenol disinfection.…”
Section: As the Main Disinfectant Of Uf Effluentmentioning
confidence: 99%